Conventional wisdom, meta-analysis, and research revision in economics - Sebastian Gechert; Bianka Mey; Matej Opatrny; Tomáš Havránek; Tom D. Stanley; Pedro R. D. Bom; Chris Doucouliagos; Philipp Heimberger; Zuzana Irsova; Heiko J. Rachinger (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
Over the past several decades, meta-analysis has emerged as a widely accepted tool to understand economics research. Meta-analyses often challenge the established conventional wisdom of their respective fields. We systematically review a wide range of influential meta-analyses in economics and compare them to 'conventional wisdom.' After correcting for observable biases, the empirical economic effects are typically much closer to zero and sometimes switch signs. Typically, the relative reduction in effect sizes is 45-60%.
Keywords: A14; B40; C10; 330; meta-analysis; systematic review; conventional wisdom